Expression of oestrogen receptor β and prognosis of colorectal cancer - Rudolph, Anja; Tóth, Csaba; Hoffmeister, Michael; Roth, Wilfried; Herpel, Esther; Jansen, Lina; Marx, Alexander; Brenner, Hermann; Chang-Claude, Jenny (British journal of cancer, 2012)
Background: Previous studies suggest that sex steroids influence colorectal cancer (CRC) carcinogenesis. The oestrogen receptor β (ERβ) is the predominantly expressed ER in the colon and loss of ERβ in CRC has been associated with advanced cancer stages. Methods: Information on vital status by the end of 2009 was obtained for 1262 CRC patients recruited between 2003 and 2007. The ERβ expression was immunohistochemically measured and associations of ERβ scores with overall survival (OS), disease-specific survival (DSS) and disease-free survival (DFS) were evaluated using Cox proportional hazard models adjusted for prognostic factors, such as tumour stage and second primary tumours. Results: Of the 1101 tumour samples with successful measurement, 535 were ERβ negative (48.6%), 381 (34.6%) showed moderate and 185 (16.8%) showed high ERβ expression. Compared with high ERβ expression, lack of ERβ was associated with higher cancer stages as well as greater tumour extent. In multivariate analyses, ERβ negativity was associated with an increased hazard ratio for death (HR=1.61, 95% CI 1.09-2.40, P=0.02), death attributed to CRC (HR=1.54, 95% CI 0.99-2.39, P=0.06) as well as a poorer DFS (DFS HR=1.64, 95% CI 1.23-3.36, P=0.04). The associations were stronger in stage I-III patients (OS HR=2.20, 95% CI 1.28-4.06, P=0.007, DSS HR=2.38, 95% CI 1.20-5.39, P=0.02, respectively). Conclusions: Lack of ERβ expression is associated with advanced cancer stages and independently associated with poor survival.